Corporate disputes in the Republic of Kazakhstan: Their Features and Methods of Resolution - ALEXEYEVA, Snezhana Vladimirovna; TYNYBEKOV, Serikkali Tynybekovich (Journal of Advanced Research in Law and Economics; Vol 9 No 1 (2018): JARLE Volume IX Issue 1(31) Spring 2018, 2018)
Currently, the problem of corporate disputes between Kazakh companies, as well as disputes with the participation of foreign investors is topical. The article is devoted to consideration of the legal nature of corporate disputes, delineation of such concepts as ʼcorporate conflictʼ, ʼconflict of interestsʼ, ʼeconomic disputeʼ. The author analyzes the history of the origin of corporate conflicts, considers ways of resolving corporate conflicts, both in judicial and extrajudicial order, including with the help of a modern institution of mediation. Thus, the main objective of the study is the legal regulation of corporate legal relations in joint-stock companies in the Republic of Kazakhstan, including in the field of the emergence and resolution of corporate conflicts involving various subjects.